Molecular Insights Into Memory-Enhancing Metabolites of Nicotine in Brain: A Systematic Review - Majdi, Alireza; Kamari, Farzin; Sadigh-Eteghad, Saeed; Gjedde, Albert (Frontiers in Neuroscience, 2019)
Background: The alleged procognitive effects of nicotine and its metabolites in brain are controversial. Objective: Here, we review the pharmacologically active biotransformations of metabolites of nicotine in brain and their effects on cognitive performance and related neuronal mechanisms. Methods: We searched Embase, Medline via PubMed, Scopus and Web of Science databases for entries no later than 2017, and restricted the search to articles about nicotine metabolites and cognitive behaviour or cognitive mechanisms. Results: The initial search yielded 425 articles, of which 17 were eligible for inclusion after application of exclusion criteria. Of these, 13 were experimental, two were clinical, and two were conference papers. Conclusions: The results revealed three pharmacologically active biotransformations of nicotine in the brain, including cotinine, norcotinine, and nornicotine, among which only cotinine had significant procognitive impact without adverse effects.